A Bi-Factor Approach to Modeling the Structure of Worry and Rumination. Issue 3 (July 2017) - Hur, Juyoen; Heller, Wendy; Kern, Justin L.; Berenbaum, Howard
It remains unclear whether worry and rumination represent the same functional process, or if they are unique constructs. The current study examined the relationship between worry and rumination, focusing on the potential utility of a bi-factor approach as an alternative to "common" vs. "distinctive" approaches. The results indicated that the structural relationship between worry and rumination is best represented by a bi-factor model (compared to single-factor and two-factor models), which is comprised of a single factor that captures common variance in worry and rumination, as well as separate worry-specific and rumination-specific factors that capture unique variance. Furthermore, three orthogonal factors derived from the bi-factor model showed diverging associations with motivational traits (avoidance and approach temperament) and distinct anxiety/depression symptoms. The bi-factor conceptualization provides a framework for reconciling the diverging perspectives regarding worry and rumination, suggesting the need to pay attention to both common and unique aspects of worry and rumination.